Highly Efficient Coaxial TiO2‐PtPd Tubular Nanomachines for Photocatalytic Water Purification with Multiple Locomotion Strategies. (2nd August 2016) - Mushtaq, Fajer; Asani, Agim; Hoop, Marcus; Chen, Xiang‐Zhong; Ahmed, Daniel; Nelson, Bradley J.; Pané, Salvador
Abstract : Titania is a promising photocatalyst for water purification or production of solar fuels. However, due to its large band gap, titania is photoactive solely under UV light, which accounts for less than 5% of the solar spectrum. In this work, TiO2 ‐based hybrid 1D nanostructures with photocatalytic activities extended to visible light region are designed and fabricated. Highly efficient coaxial TiO2 ‐PtPd‐Ni nanotubes (NTs) are fabricated by a template‐assisted electrochemical synthesis route for water remediation under UV light, visible light, and natural sunlight. These coaxial hybrid nanotubes display a 100% degradation of organic pollutant rhodamine B in only 50 min ( k ‐value 0.071 min −1 ) and 30 min under visible light and natural sunlight, respectively. For comparison, TiO2 nanotubes doped with Pd nanoparticles are also fabricated and they show inferior photocatalytic properties and degrading stability over time. The multicomponent design enables to actuate the hybrid NTs by using two different external energy sources, i.e., magnetic and acoustic fields. Self‐propelled, autonomous actuation in the presence of H2 O2 is also realized. These versatile actuation modes have the potential to enable the reported photocatalytic nanomachines to work efficiently under complex environments and to be easily collected for reuse. Abstract : Coaxial TiO2 ‐PtPd‐Ni hybrid nanotubes exhibit greatly enhanced visible light photocatalyic activity: a 100% degradation of organic pollutant under visible and natural sunlight with high stability. Combined with multiple locomotion strategies, these highly efficient and cost‐effective hybrid photocatalytic nanomachines have the potential to be reused for practical water remediation applications in complex and challenging environments.